Peutz-Jehger’s Syndrome presenting as adult intussusception - Athar, Z; Rajbhandri, A; Kansakar, P; Singh, P; Vaidya, P (Journal of Institute of Medicine Nepal, 2009)
Peutz-Jehger's syndrome is an autosomal dominant disorder. It is the second most common hamartomatous syndrome with hamartomatous polyp of gastrointestinal tract and cutaneous melanin deposit. Majority of patients remain relatively asymptomatic. Some present with abdominal pain secondary to obstruction or impending obstruction owing to an intussuscepted polyp with GI bleeding. We report a case of 21 year male who presented with upper central abdominal pain, distension, vomiting and blood mixed stool. He also had black colored spots on perioral region and fingers. Ultrasound revealed mass lesion with echogenic centre suggestive of intussusception. Emergency laparotomy revealed jejunojejunal intususception with gangreneous intussusceptum and two other large polyps. Resection anastomosis of jejunum and excision of polyps was done. Peutz-Jehger's syndrome is a rare but important cause of intussusception in adults presenting with cutaneous manifestations and features of intestinal obstruction. Key words: Cutaneous melanin, Hamartomatous polyp, Intussusception, Peutz-Jegher's syndrome The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, April, 2009; 31:1 30-32